The effect of temperature on wear and friction of a high strength steel in fretting - Pearson, S.R.; Shipway, P.H.; Abere, J.O.; Hewitt, R.A.A. (Elsevier, 2013)
This paper investigates the effect of temperature (between 24 °C and 450 °C) on the wear rate and friction coefficient of a high strength alloy steel (Super-CMV) in gross sliding fretting in air. It was found that whilst there was significant loss of material from the contact during fretting at room temperature, the overall loss of material from the contact had become negative even with a modest increase in temperature to 85 °C. At temperatures greater than 85 °C, negative wear was maintained, with the coefficient of friction dropping monotonically with increasing temperature up to 450 °C. It is proposed that the changes in wear rate and friction coefficient were due to changes in the way that the oxide particles sintered to form a protective debris bed, with sintering of the oxide debris particles at these low temperatures being promoted by the nano-scale at which the oxide debris is formed.